The Influence of Scrabble Game Towards Vocabulary Mastery for Young Learners (Study Case In Al-Irsyad Quran House Lappa) - Harmilawati; Khaerunnisa; Yunitasari; Zahrawati (Universitas Islam Ahmad Dahlan (UIAD), 2021)
This research aims to know the influence of the application of the Scrabble game in learning English to know the increase in the vocabulary of the Al-Irsyad Quran House Lappa using the Scrabble game. The researchers use the quantitative methods, through techniques random sampling and focused on one group. The type of research is pre-experimental design. Through the application of pre-test and post-test designs. The instrument used in this research is a short objective test with a total of 10 items that have been randomized through content validity because the preparation of the instrument is adjusted to the material taught to students. Students experienced a significant increase in the vocabulary category as evidenced before the pretest, more students were included in the Enough category as many as 11 students or 44%, while in Excellent and Very good categories, there were only 2 students each who proved their vocabulary mastery was still low. After applying the Scrabble game, students experienced an increase, it can be seen in the Insufficient category that there were no more students who got a score of 60. This increased in the Excellent and Very Good categories which initially only 2 students, after the post-test the Excellent category was 11 students or (44% ) funds in the Very Good category were 7 students (28%) of 25 students.